Sulphur removal in ironmaking and oxygen steelmaking. (28th May 2017) - Schrama, Frank Nicolaas Hermanus; Beunder, Elisabeth Maria; Van den Berg, Bart; Yang, Yongxiang; Boom, Rob
Abstract : Sulphur removal in the ironmaking and oxygen steelmaking process is reviewed. A sulphur balance is made for the steelmaking process of Tata Steel IJmuiden, the Netherlands. There are four stages where sulphur can be removed: in the blast furnace (BF), during hot metal (HM) pretreatment, in the converter and during the secondary metallurgy (SM) treatment. For sulphur removal a low oxygen activity and a basic slag are required. In the BF typically 90% of the sulphur is removed; still, the HM contains about 0.03% of sulphur. Different HM desulphurisation processes are used worldwide. With co-injection or the Kanbara reactor, sulphur concentrations below 0.001% are reached. Basic slag helps desulphurisation in the converter. However, sulphur increase is not uncommon in the converter due to high oxygen activity and sulphur input via scrap and additions. For low sulphur concentrations SM desulphurisation, with a decreased oxygen activity and a basic slag, is always required.